The association of vitamin D status and dietary calcium intake with individual components of the metabolic syndrome: a population-based study in Victoria, Australia. Issue 4 (December 2017) - Pannu, Poonam K.; Soares, Mario J.; Piers, Leonard S.; Zhao, Yun; Ansari, Zahid
Abstract : Objective: This study examined the associations between 25-hydroxyvitamin D (25-OHD), dietary calcium (Ca) intake, and individual components of the metabolic syndrome (MetS). Methods: We analyzed a population-based sample of 18–75-year-old adults ( n =3387) from the Victorian Health Monitor survey. Results: After adjustment for sociodemographic, physical, and dietary factors, as well as other MetS components, every 10 nmol/l increment in 25-OHD was associated with reduced adjusted odds ratio (AOR) of elevated triglycerides (TG) [AOR: 0.79, 95% confidence interval (CI): 0.74–0.84, P <0.001], and higher fasting plasma glucose (AOR: 0.91, 95% CI: 0.86–0.96, P =0.002). After adjustment for confounders, every 500 mg/day increment in dietary Ca intake significantly reduced the odds of elevated diastolic blood pressure (AOR: 0.80, 95% CI: 0.66–0.99, P =0.038). When nine combinations of 25-OHD and Ca tertiles were examined, certain combinations were associated with reduced AOR for elevated TG ( P <0.001), when referenced against the combination of low 25-OHD (median: 33 nmol/l) and low Ca (median: 579 mg/day). At low 25-OHD, increasing Ca intake decreased the AOR for low high-density lipoprotein cholesterol in a dose-dependent manner, but at high 25-OHD; such effects of Ca were blunted. Conclusion: Higher vitamin D status and Ca intake or their combination were associated with reduced odds for a number of individual MetS components.